2021
DOI: 10.1021/acs.jpca.0c11490
|View full text |Cite
|
Sign up to set email alerts
|

Thermal Decomposition of 2-Methyltetrahydrofuran behind Reflected Shock Waves over the Temperature Range of 1179–1361 K

Abstract: The thermal unimolecular decomposition of 2methyltetrahydrofuran (2-MTHF) was studied behind reflected shock waves in a single-pulse shock tube over the temperature range of 1179−1361 K and pressure range of 9−17 atm. Methane, ethylene, ethane, 1,3-butadiene, propylene, acetaldehyde, and acetylene were identified as products in the decomposition of 2-MTHF. A reaction scheme was proposed to explain the mechanism for the observed products. The experimentally determined rate coefficients were best fit to an Arrhe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 72 publications
2
1
0
Order By: Relevance
“… 11 The potential energy surface shows that 2-methyltetrahydrofuran-5-yl produces CO and n -butyl by ring-opening, H-transfer, and decarbonylation of the α-pentanal radical intermediate. Similar decarbonylation reactions were observed in decomposition of α-aldehyde radicals 28 and cyclic ether species, 29 , 30 and further evidenced in experiments of Rajakumar et al, 31 which indicated an unknown source of carbon monoxide during thermal decomposition of 2-methyltetrahydrofuran in a shock tube.…”
Section: Resultssupporting
confidence: 74%
See 1 more Smart Citation
“… 11 The potential energy surface shows that 2-methyltetrahydrofuran-5-yl produces CO and n -butyl by ring-opening, H-transfer, and decarbonylation of the α-pentanal radical intermediate. Similar decarbonylation reactions were observed in decomposition of α-aldehyde radicals 28 and cyclic ether species, 29 , 30 and further evidenced in experiments of Rajakumar et al, 31 which indicated an unknown source of carbon monoxide during thermal decomposition of 2-methyltetrahydrofuran in a shock tube.…”
Section: Resultssupporting
confidence: 74%
“…12 The potential energy surface shows that 2methyltetrahydrofuran-5-yl produces CO and n-butyl by ringopening, H-transfer, and decarbonylation of the α-pentanal radical intermediate. Similar decarbonylation reactions were observed in decomposition of α-aldehyde radicals 29 and cyclic ether species, 30,31 and further evidenced in experiments of Rajakumar et al, 32 which indicated an unknown source of carbon monoxide during thermal decomposition of 2-methyltetrahydrofuran in a shock tube. Both unsaturated alkoxy radicals (1-pentene-4-oxy and 2pentene-4-oxy from R1 and R3 ring-opening, respectively) can undergo methyl loss via β-scission, yet over relatively higher barriers compared with other pathways.…”
Section: ■ Results and Discussionsupporting
confidence: 73%
“…It is known that compounds with a larger HOMO-LUMO gap and chemical hardness are more resistant to undergoing chemical reactions or to being transformed by an external perturbation, such as an applied electric field. On the other hand, a low chemical softness value denotes a high tendency of the molecule to degrade, while a higher electronegativity reflects a higher tendency of the compound to form a bond [72,73]. The activation energy of the compounds was also evaluated, as the difference in the total energies of transitional and ground states.…”
Section: Methodsmentioning
confidence: 99%